Membangun Generasi Cerdas Dan Berakhlak: Kontribusi Muhammadiyah Dalam Pendidikan Modern - Siti Nur Anissa; Lola Amanda; Himarani Hidayatulloh Yudhomiranti; Haura Zahrah Sudirman; Agus Setya Wardhana; Astika Nurul Hidayah (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Islamic education has a broad scope that includes intellectual, emotional, and spiritual aspects, with the aim of forming individuals who are faithful, pious, and have noble character. One organization that consistently integrates Islamic values in education is Muhammadiyah. Since its establishment in 1912, Muhammadiyah has developed an education system that combines religious and general knowledge, focusing on character building, morals, and intellectual intelligence. In facing the digital era, Muhammadiyah adopts modern technology through online learning, innovation programs such as Edutabmu, and digital training for teachers. A curriculum that integrates Islamic values with technology-based learning supports the creation of a young generation that is smart, characterized, and responsive to the challenges of the times. The success of Muhammadiyah character education is reflected in the formation of individuals with high integrity, have noble personalities, and are able to contribute positively to society..